Spatial variation of stomatal morphological traits in grassland plants of the Loess Plateau. (September 2021) - Sun, Jingguo; Liu, Congcong; Hou, Jihua; He, Nianpeng
Highlights: Stomata control carbon and water fluxes in leaves and help plant adapt environment. We measured stomatal density (SD) and size (SS) for 181 species in Loess Plateau. Stomatal traits differ across grassland types and plant functional groups. The responses of stomata to the environment result from tradeoff between SD and SS. The adaptation of stomata in adaxial epidermis to environment is regulated by SS. Abstract: The stomata control carbon and water vapor exchange between the leaves and atmosphere and may reflect plant adaptation to climate change to some extent. However, the spatial variation of stomatal traits on different sides of the leaves' epidermis and their response to environmental changes remain unclear. Here, we measured stomatal density (SD), stomatal size (SS), and stomatal relative area (SRA) on both leaf surfaces of 181 plant species across an environmental gradient on the Loess Plateau. We calculated the proportion of stomatal traits between different epidermis surfaces of the leaves (abaxial and adaxial) and measured the total SD (SDtot ), total SS (SStot ), and total SRA (SRAtot ) of the leaves as a whole. The SDtot, SStot, and SRAtot showed a log-normal distribution, differing across grassland types and plant functional groups, with a range of 22.57–890.09 stomata mm −2, 84.61–2022.81 μm 2, and 0.51–43.71%, respectively. The SDtot, SStot, and SRAtot differed significantly between different grassland types. Meadow plants had larger SDtot, desert plants had larger SStot, and typical grassland plants had relatively larger SRAtot. The abaxial SD and SRA of the woody plants were significantly higher than those of herbaceous plants, but no significant differences were observed at the adaxial surface or for the overall leaf. A higher SDtot was correlated with a larger stomatal density ratio (R.SD) and smaller stomatal size ratio (R.SS). The R.SD, abaxial SD, abaxial SS, and adaxial SS were significantly correlated with environmental factors, but no such correlations were observed for the adaxial SD. These findings highlight the strong associations of stomatal traits with plant functional group and climate at a regional scale, representing the climatic adaptation strategies of stomatal traits across natural grassland communities.